The physics of galaxy formation - Lagos, Claudia Del P. (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2014)
This thesis addresses two of the central processes which underpin the formation of galaxies: the formation of stars and the injection of energy into the interstellar medium from supernovae, called feedback. In her work Claudia Lagos has completely overhauled the treatment of these processes in simulations of galaxy formation. Her thesis makes two major breakthroughs, and represents the first major steps forward in these areas in more than a decade. Her work has enabled, for the first time, predictions to be made which can be compared against new observations which probe the neutral gas content of galaxies, opening up a completely novel way to constrain the models. The treatment of feedback from supernovae, and how this removes material from the interstellar medium, is also likely to have a lasting impact on the field. Claudia Lagos Ph.D. thesis was nominated by the Institute for Computational Cosmology at Durham University as an outstanding Ph.D. thesis 2012.